Processing windows for Ti-6Al-4V fabricated by selective electron beam melting with improved beam focus and different scan line spacings - Pobel, Christoph; Osmanlic, Fuad; Lodes, Matthias; Wachter, Sebastian; Körner, Carolin (Rapid Prototyping Journal, 2019)
Purpose: Selective electron beam melting (SEBM) is a highly versatile powder bed fusion additive manufacturing method. SEBM is characterized by high energy densities which can be applied with nearly inertia free beam deflection at high speeds (<8.000 m/s). This paper aims to determine processing maps for Ti-6Al-4V on an Arcam Q10 machine with LaB6 cathode design. Design/methodology/approach: Scan line spacings of 100, 50 and 20 µm in a broad parameter range, focusing on high deflection and build speeds are investigated. Findings: There are broad processing windows for dense parts without surface flaws for all scan line spacings which are defined by the total energy input and the area melting velocity. Originality/value: The differences and limitations are discussed taking into account the beam properties at high beam energy and velocity as well as evaporation related loss of alloying components.
CRIS-Team Scopus Importer:2021-04-20
Keywords: CAD; Metals; Rapid prototyping; Research; Selective electron beam melting; Titanium